Refractory reactivated VZV encephalitis with vasculopathy secondary to rituximab - Nisha A. George; Melissa Haines; Vincent Lam; Julian Tang (Clinical Infection in Practice)
We report a case of a 54 year old Sudanese lady admitted with dizziness, visual disturbance and collapse with nystagmus, ataxia, bilateral ptosis, and 3rd cranial nerve palsy on examination. CT and MRI scan of her head showed multiple areas of infarct. A lumbar puncture showed lymphocytosis and was positive for VZV. She was initiated on treatment with IV acyclovir but during the course of her admission, she had recurrent strokes and maintained VZV DNA positivity on repeated lumbar punctures despite being on prolonged treatment. She was diagnosed with refractory varicella encephalitis secondary to varicella zoster virus reactivation, likely resulting from recent rituximab therapy for systemic lupus erythematosus and a mixed connective tissue disorder.